The Impact of Green Product on the Customer Purchasing Behavior: An Analytical Study on a Sample of the Technological Companiesat Amman (Global Journal of Management and Business Research, 2014)
Abstract not found
Keywords: green product; customer purchasing behavior; technological companies; amman